Real-time nanomechanical and topographical mapping on live bacterial cells-brevibacterium casei under stress due to their exposure to Co2+ Ions during microbial synthesis of Co3O4 nanoparticles - Kumar, Umesh; Vivekanand, K.; Poddar, Pankaj (Journal of Physical Chemistry B, 2009)
The study of elastic properties of microbial and mammalian cells using atomic force microscopy, with force-sensitivity as high as pico-Newtons and spatial resolution of a few nanometers, is proving to be a great tool for the real-time observation of the effects of drugs, biomolecules, metal ions, and nanoparticles on cell physiology in their natural environment. It has been shown that the Young's modulus of the cell surfaces is extremely sensitive to the surrounding environment. Recently, a broad array of microbes have been used successfully to synthesize nanocrystals of several metal and metal oxides in a controlled manner at room temperature after exposing them to various metal ion precursors. However, so far there is no report on the fate of their elastic properties and cell topography etc. during and after their exposure to the metal ions during the microbial synthesis of nanomaterials. Additionally, this information is also found to be extremely relevant to areas such as bioremediation, bioleaching, and biomineralization, where it is important to study the direct influence on the cell physiology in the presence of metal ions. Here, we report, for the first time, the use of AFM force-distance curves on live cells, to directly monitor (in real time) the changes in the surface-topography, surface-adhesion, indentation-depth, and Young's modulus of a metal-tolerant marine bacterium, Brevibacterium casei, isolated from the coast of the Arabian Sea, after its exposure to the Co2+ ions during the process of biosynthesis of nanoparticles. We earlier reported that this bacterium is capable of using the cobalt acetate as a precursor to synthesize protein-functionalized Co3O4 nanoparticles with very high crystallinity. Our study indicates a significant change in the morphology as well as elastic and adhesive properties of the Brevibacterium casei, where we found an increase in the adhesive properties and the indentation depth of the bacterial surfaces and a decrease in the cell stiffness after several hours of exposure to the cobalt acetate. We have discussed both qualitative and quantitative analysis of the force-spectroscopy data in detail.

Effect of reduced particle size on the magnetic properties of chemically synthesized BiFeO3 nanocrystals - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Here, we report the effect of reduction in particle size on the temperature dependent magnetization of chemically synthesized BiFeO3 nanocrystals with average grain size of 55 nm. The X-ray photoelectron spectroscopy results show a significant broadening of binding energy peaks associated to Fe3+ 2p(3/2) core levels due to the reduced size. Additionally, due to the nanosize effect, the M-H loops show a significant coercivity starting from 390 K with an anomaly located in the vicinity of 150 K in our H-c vs T as well as M-r/M-s(50 kOe) vs T curves. At this temperature, both H-c and M-r/M-s(50 kOe) undergo minima. Additionally, our results for the first time show the evidence of existence of a low temperature anomaly due to spin-glass transition in the range from 40-44 K in the field cooled magnetization curves. In bulk single crystals, this transition is reported to be situated at around 50 K, however, this transition remained so far undiscovered in the recent studies on BiFeO3 nanoparticles due to the insufficient temperature resolution. The significant shift in this transition toward lower temperature can be attributed to size dependent effects. Our results clearly present new information on the size dependent properties of BiFeO3 nanoparticles.

Fabrication of homogeneous nanoparticle/nanoneedle BaTiO3 and Ba0.8Sr0.2TiO3 smooth thin films by simple dip coating - Saini, Mamta; Vivekanand, K.; Poddar, Pankaj; Murty, K. V. G. K.; Thushara, K. S.; Gopinath, Chinnakonda S. (International Journal of Nanotechnology, 2010)
Ferroelectric BaTiO3 (BTO) and Ba0.8Sr0.2TiO3 (BSTO) thin film materials have been successfully prepared by sol-gel processing and simple dip coating on glass and silicon supports. Above thin films were characterised by x-ray diffraction (XRD), Raman spectroscopy, photoelectron spectroscopy, thermal analysis, atomic force microscopy (AFM) and spectroscopic ellipsometry. Phase identification of BaTiO3 and Ba0.8Sr0.2TiO3 was performed by XRD. XRD and Raman spectroscopy investigations demonstrate that thc Ba0.8Sr0.2TiO3 film exhibits tetragonal structure. AFM analysis demonstrates the elongated nanospherical particles on glass substrate and nanowires on silicon substrate, which represent a strong influence of the crystallinity of underlying substrate on the grain morphology in this technique. The thin films on both the substrates are uniformly coated without any pinhole to significant area (similar to 2.5 cm(2)), and this method might be extended to large area uniform coating. Spectroscopic ellipsometric measurements reveal the exact thickness, refractive index and extinction coefficient of the thin films.
Keywords: barium strontium titanate; barium titanate; dip coating; fabrication; ferroelectric material; large area coating; nanotechnology; thin film

Magnetic and dielectric properties and Raman spectroscopy of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Maity, Tuhin; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2010)
The rare earth orthochromites are extremely interesting due to the richness of their optical, dielectric, and magnetic properties as well as due to their multiferroic properties which make them suitable materials to study in the nanoregime. However, the wet-chemical synthesis of these materials in nanosize is nontrivial. Here, we report for the first time, the detailed Raman spectra as well as magnetic and dielectric properties of chemically synthesized GdCrO3 nanoparticles of size ranging from 40 to 60 nm. The magnetic properties are dictated by competing Cr3+-Cr3+, Gd3+-Cr3+, and Gd3+-Gd3+ superexchange interactions in different temperature regions, resulting into an antiferromagnetic ordering at 167 K due to the Cr3+-Cr3+ followed by weak ferromagnetic ordering due to the onset of Cr3+-Gd3+ interactions. At lower temperature, it shows weak antiferromagnetic ordering due to Gd3+-Gd3+ interaction. Below 95 K, GdCrO3 nanoparticles showed the presence of negative magnetization due to Gd3+ and Cr3+ interactions resulting into weak ferromagnetic coupling. The Raman spectroscopy shows the characteristic Raman shifts indicating that below 450 cm(-1), Gd3+ ions play a dominant role in determining the phonon frequencies of GdCrO3, and above 450 cm(-1), the Cr+3 ions dominate. We also present for the first time the low temperature dielectric constant and loss tangent data for GdCrO3 in a broad temperature and frequency range. The dielectric constant shows a decrease in comparison to the bulk values due to the size dependent effects. It also shows a peak centered at around 320 K above which it shows a sharp decrease. The dielectric loss value in GdCrO3 nanoparticles is quite small and shows an interesting frequency dependent anomaly at lower temperature which might be due to the coupling between magnetic and dielectric order parameters.
Keywords: dielectric losses; gadolinium compounds; Magnetisation; Multiferroics; nanofabrication; Nanoparticles; permittivity; phonons; Raman spectra; superexchange interactions

Temperature-dependent raman and dielectric spectroscopy of BiFeO3 nanoparticles: signatures of spin-phonon and magnetoelectric coupling - Jaiswal, Adhish; Das, Raja; Maity, Tuhin; Vivekanand, K.; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
We report the temperature-dependent Raman and dielectric spectroscopy of chemically synthesized BiFeO3 nanoparticles (average size similar to 50-60 nm). The Raman spectra (90-700 K) show two sets of transitions in the lowest Raman E mode, associated with Bi-O bond motion situated in close proximity to the spin reorientation transitions reported for BiFeO3, thereby indicating the existence of possible coupling between magnons and phonons for particle size below the helical order parameter (62 nm). These transitions are slightly shifted in temperature in comparison to the bulk single crystals. We also observe a step-like behavior in Raman peak position around the Neel temperature, suggesting that the phonons are influenced by the magnetic ordering in nanosized BiFeO3. The heat-flow measurements show two sharp endothermic peaks at 1094 and 1223 K representing rhombohedral to orthorhombic or monoclinic transition followed by transition into the cubic phase above 1200K. The low temperature (20-325 K), frequency-dependent (1-10(6) Hz) dielectric constant and loss tangent measurements show that the loss tangent (similar to 10(-3)) and ac conductivity values (similar to 10(-8) Ohm(-1)-cm(-1)) are orders of magnitude lower than the reported values for BiFeO3 ceramics, indicating high levels of ionic purity of our samples. The real part of the permittivity shows a slight reduction in its value (similar to 30) in comparison to the bulk single crystals. Similar to the Stokes Raman shift, its temperature-dependent dielectric constant also shows four weak anomalies at similar to 85, 168, 205, and 230 K situated in close proximity to the spin reorientation transitions, indicating magnetoelectric coupling.